The shack : a novel - Young, William P. (Newbury Park, Calif. : Windblown Media, 2007)
Mackenzie Allen Phillips' youngest daughter, Missy, has been abducted during a family vacation and evidence that she may have been brutally murdered is found in an abandoned shack deep in the Oregon wilderness. Four years later in the midst of his Great Sadness, Mack receives a suspicious note, apparently from God, inviting him back to that shack for a weekend. Against his better judgment he arrives at the shack on a wintry afternoon and walks back into his darkest nightmare. What he finds there will change Mack's world forever. In a world where religion seems to grow increasingly irrelevant, "The Shack" wrestles with the timeless question, "Where is God in a world so filled with unspeakable pain?" The answers Mack gets will astound you and perhaps transform you as much as it did him.
A confluence of paths -- The gathering dark -- The tipping point -- The great sadness -- Guess who's coming to dinner -- A piece of "pi" -- God on the dock -- A breakfast of champions -- A long time ago, in a garden far, far away -- Wade in the water -- Here come da judge -- In the belly of the beasts -- A meeting of hearts -- Verbs and other freedoms -- A festival of friends -- A morning of sorrows -- Choices of the heart -- Outbound ripples -- After words.
Keywords: Life change events -- Fiction; Missing children -- Fiction; Oregon -- Fiction; Religious fiction; Suspense fiction